OVERVIEW THE LAW OF ZAKAT PAYMENT USES FINTECH IN ISLAMIC PERSPECTIVE - Ghofur, Ruslan Abdul; Ichwan, Afiful (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2020)
The current development of technology 4.0 has made many major changes, especially in the transaction model. The presence of Financial Technology (Fintech) has transformed cash transactions into a non-cash transaction model that can be done without having to meet face to face. This gives people the convenience of making transactions. Not only in transactions of economic activity, but also non-cash payment through Fintech have been used in paying zakat. The purpose of this research is to find out how the laws of Fintech are used to pay zakat. In this study, the authors used a literature study research method, namely by searchingfor documents such as national and international journals, books, and websites related to research. The results of the analysis using the nine principles of Islamic law conclude that legal fintech itself is allowed as long as the transaction does not contradict sharia principles and does not contain elements of danger.